A study of the healthcare resource use for the management of postpartum haemorrhage in France, Italy, the Netherlands, and the UK. (January 2022) - Richardson, Jessica; Hollier-Hann, Georgia; Kelly, Kathryn; Chiara Alvisi, Maria; Winter, Cathy; Cetin, Irene; Draycott, Timothy; Harvey, Thierry; Visser, Gerard H.A.; Yip Sonderegger, Yum L.; Perroud, Julie
Highlights: Postpartum haemorrhage (PPH) is associated with increased healthcare resource use. Additional medical interventions are required following PPH. Additional healthcare personnel are involved in the management of PPH. Major PPH can lead to an additional 24 h spent hospital vs uncomplicated birth. Abstract: Objective: Postpartum haemorrhage (PPH) complicates approximately 5% of births worldwide and is a leading direct cause of maternal death. Rates of PPH are increasing in many developed countries, particularly PPH related to uterine atony. There is a lack of published up-to-date information about healthcare resource use associated with management of PPH following vaginal birth. The objective of this study was to describe healthcare resource use for the management of minor PPH (blood loss 500–1, 000 ml) and major PPH (blood loss > 1, 000 ml) compared to uncomplicated birth (no PPH) following hospital vaginal birth in France, Italy, the Netherlands, and the UK. Study design: In-depth interviews with two midwives from each participating country were conducted to establish differences in resource use for the management of minor PPH, major PPH, and uncomplicated birth. A web-survey was then developed and one obstetrician per participating country reviewed the survey. In total, 100 midwives (25 per country) completed the survey. Results were discussed at a multi-professional consensus meeting of midwives and obstetricians/gynaecologists (n = 6). Results and conclusions: Midwives participating in the survey estimated that 80% of women receive Active Management of the Third Stage of Labour (AMTSL) and 93% of participants specified that uterotonics would routinely be used during AMTSL. Most participants (84%) reported that blood loss is routinely measured in their hospital, using a combination of methods. PPH is associated with increased healthcare resource use, including administration of additional uterotonics and use of additional medical interventions, such as urinary catheter, intravenous fluids, and possible requirement for surgery. The number of nurses, obstetricians/gynaecologists, and anaesthetists involved in the management of PPH increases with the occurrence and severity of PPH, as well as the proportion of healthcare personnel providing continuous care. Women may spend an additional 24 h in hospital following major PPH compared to uncomplicated birth. The results of this study highlight the burden of PPH management on healthcare resources. To reduce costs associated with PPH, prevention is the most effective strategy and can be enhanced with the use of an effective uterotonic as part of the active management of the third stage of labour.